ULTRASONIC-ASSISTED EXTRACTION OF ANTIOXIDANT PHENOLIC COUMPOUNDS FROM EUCHEUMA COTTONII - Dyah Hesti Wardhani; Denni Kartika Sari; Aji Prasetyaningrum (Reaktor, 2013)
The influences of ultrasonic-assisted extraction (UAE) conditions on phenolic compounds of Eucheuma cottonii seaweeed were investigated. The effects of temperature, time and liquid-solid ratio were evaluated based on the total phenolic content (TPC). The result showed a significant variability of effect of temperature, time, and liquid-solid ratio on TPC. Application of ultrasound reduced the optimum temperature, time and liquid-solid ratio of the extraction when compared to the conventional extraction. The highest phenolic content (4.44 mg gallic acid equivalent/g dry weight) was obtained at 3:1(v/w) of liquid-solid ratio, 55oC of temperature and 35 min of extraction time. At this condition, the extract showed ability to scavenging 91% of 1,1-diphenyl 2 picrylhydrazyl (DPPH radical) and 10.9% of H2O2. High ability of the extract to scavenge DPPH radical but low in scavenging H2O2 indicated that the extract dominated by primary antioxidant compounds which work by donating hydrogen atoms to bind free radical.